Cost per responder for ixekizumab and other biologic drugs approved for the treatment of moderate-to-severe plaque psoriasis in Italy - Roberto Ravasio; Silvia Antonelli; Alessia Maiorino; Antonio Costanzo; Serena Losi (Global & Regional Health Technology Assessment, 2019)
This analysis was aimed at estimating the cost per responder as measured by number needed to treat of ixekizumab as compared with other biologic drugs approved in Italy for the treatment of moderate-to-severe plaque psoriasis. The clinical efficacy was assessed in terms of number needed to treat, based on a network meta-analysis of published efficacy data as measured by Psoriasis Area and Severity Index response (PASI75, PASI90, and PASI100) for relevant biologic comparators. The cost was based on the number of administrations dispensed in the first (induction plus maintenance period) and the second (maintenance period only) year of treatment and the ex-factory price net of discounts of each biologic drug. The cost per responder was adopted as a cost-effectiveness indicator. Independent of the Psoriasis Area and Severity Index response (PASI75, PASI90, and PASI100) used and the year of treatment considered, the cost per number needed to treat for ixekizumab appeared consistently to be the lowest. For example, considering first-year costs and PASI75, the cost per responder for ixekizumab was €16,388, compared to adalimumab (€22,574), etanercept (branded original: €32,420; biosimilar: €21,432), secukinumab (€17,937), and ustekinumab (€20,014). The differences in the cost per responder between ixekizumab and the comparators increased when higher Psoriasis Area and Severity Index response levels were considered. This economic assessment confirmed that ixekizumab is a cost-efficient option from the perspective of the Italian National Health Service for the treatment of moderate-to-severe plaque psoriasis.